Aves que habitan horizontes portátiles. Competencia ornitológica en la poesía de César Vallejo - López Carballo, Pablo (2024)
The main objective of this article is to analyze the ornithological competence of César Vallejo's poetic work. The poet's treatment of birds is useful to understand the singularity of his poetics and the meaning that this particular presence of birds brings. To do so, we will try to point out this intertwining and analyze the scope of the connections between both elements. Thus, from its links with tradition and territory to the uniqueness of the construction of his proposal, we will see how birds take on special prominence. In addition, this approach brings the possibility of understanding poetry from a social position related to ecology.